Membangun Sikap Moderasi Beragama Melalui Penanaman Nilai Budaya Lokal Tama Umma Kalada - Yohanes Umbu Lede (Ideas Publishing, 2022)
Penanaman nilai budaya lokal dalam ritual adat Tama Umma Kalada untuk membangun sikap moderasi beragama mengalami pergeseran makna. Faktor penyebab adalah era globalisasi. Perkembangan IPTEK dan minimnya pemaknaan terhadap budaya turut merubah cara pandang masyarakat Wewewa. Tujuan penelitian mengetahui nilai budaya lokal yang ditanamkan dalam ritual adat Tama Umma Kalada untuk membangun sikap moderasi beragama. Metode yang dipakai adalah metode penelitian kualitatif dengan pendekatan fenomenologi. Hasil penelitian menunjukkan bahwa penanaman nilai budaya dalam ritual adat Tama Umma Kalada yakni masyarakat masih menghidupi dan memegang erat nilai-nilai budaya seperti nilai ketaatan, solidaritas, nilai persatuan, nilai gotong royong, nilai kerja keras, nilai religius, dan toleransi serta penghormatan terhadap leluhur. The inculcation of local cultural values ​​in the traditional ritual of Tama Umma Kalada to build an attitude of religious moderation has experienced a shift in meaning. The causative factor is the era of globalization. The development of science and technology and the lack of meaning for culture have also changed the perspective of the Wewewa community. The purpose of the study was to find out the local cultural values ​​embedded in the traditional Tama Umma Kalada ritual to build an attitude of religious moderation. The method used is a qualitative research method with a phenomenological approach. Data collection technique is interview. The data analysis technique used is data triangulation. The results showed that the inculcation of cultural values ​​in the Tama Umma Kalada traditional ritual, that is, the community still lives and holds tightly to cultural values ​​such as the value of obedience, solidarity, the value of unity, the value of gotong royong, the value of hard work, religious values, and tolerance and respect for ancestors.